Meaning Of Loyalty Reflected In Let Me In Movie (2010) By Matt Reeves: An Individual Psychological Approach - Dihdairya, Duhita (2012)
The major problem of this study is to reveal how Owen's loyalties to keep his lover reflected in Let Me In movie. The objective of this study is to analyze the movie based on its structural elements and an individual psychological approach. In analysis, the writer uses qualitative method. The object of the study is Let Me In written by Steven Conrad. The data sources consist of primary and secondary data sources. The primary data source is Let Me In movie itself and the secondary data sources are the other sources related to the primary data such as the information about the director's biography, websites, and the other sources related to the analysis like theory of individual psychological by Alfred Adler. The method of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, Matt Reeves wants to describe that love can defeat anything and he wants to convey about hard work to achieve the purpose and never gives up is the important thing to get our dream. Second, based on individual psychological analysis, Matt Reeves wants to reflect that Owen's loyalties to keep his lover can produce happiness.